Tourism And Fashion: Interpreting Tourism Resources Into Fashion Product Designs in Alamendah Tourism Village - Nabilla, Affra Siti; Vyana Lohjiwa; Sukma, Mestika Nawang; Susanto, Eka; Anggrenesia, Yayang (Barista : Jurnal Kajian Bahasa dan Pariwisata, 2024)
The future of tourism destinations focuses on local communities' creativity in developing their tourist attractions, one of which is through MSMEs (Micro, Small, and Medium Enterprises). When an attraction goes viral, booming, or popular suddenly, it is followed by other destinations who imitate products without bringing out the uniqueness of the destination. On the other side, local communities want to explore new things, but on the other side, there is a fear that no tourists will be interested in visiting or purchasing products from MSMEs. This dialectical condition is the focus of the research. This research explores the various signs and meanings of tourism resources in Alamendah Tourism Village, which are realized through the creativity of MSMEs in designing fashion products. The results of this research are useful for generating product innovations that represent the village. Data were collected through field observations using a checklist, followed by data on tourism resources from the views of managers, communities, and MSME actors using in-depth interviews and integrated discussions. The results show that the resources of Alamendah Tourism Village focuses on cultural life, landscape, and coolness that symbolizes harmony and peace. The symbol was transformed into a fashion product design in the form of an outer, tote bag, and shoes with an eco print design patterned with strawberry leaves, coloured in a combination of brown, red, and green with ornaments and clump stitching techniques, the meaning are harmony and peace. This product can be applied to MSMEs actors as a creative innovation that can attract tourists to visit. This innovation is seen to be the main capital in the development of sustainable tourism that is not affected by temporary viral trend. Keywords: Alam Endah, Fashion Product Design, Innovation, MSMEs.